Assessment of phenolic contributors to antioxidant activity of new kiwifruit cultivars using cyclic voltammetry combined with HPLC. (1st December 2018) - Jiao, Yang; Kilmartin, Paul A.; Fan, Mingtao; Quek, Siew Young
Highlights: Two new kiwifruit cultivars were assessed for phenolic profile and reducing power. Cyclic voltammetry was efficient in evaluating phenolic class and reducing power. New cultivars have higher phenolic content and reducing powers than the 'Hayward'. Epicatechin was the predominant phenolic antioxidant in flesh and skins. The skins contained 3.44 fold more phenolics than flesh of the three cultivars. Abstract: The phenolics profile of two new kiwifruit cultivars, Zespri® SunGold and Zespri® Sweet Green, were characterized and quantified for the first time using cyclic voltammetry, an electrochemical method, combined with HPLC. Results from the cyclic voltammetry revealed high correlations with those obtained from the spectrophotometry and HPLC methods, providing evidence to support the application of cyclic voltammetry as a rapid method in determining the phenolic profile and reducing power of kiwifruit extracts. Catechol-containing phenolics were identified as the major phenolic sub-class in the skins while flavonoids and phenolic acids were abundant in flesh of the tested cultivars. Epicatechin was the predominant phenolic compound and contributor to antioxidant capacity in all samples. Results also showed that SunGold and Sweet Green (both flesh and skin) exhibited significantly higher phenolic contents and antioxidant activities comparing with the well-established commercial 'Hayward' cultivar, indicating their commercial value and potential applications in food and nutraceuticals.